Phase formation and performance of solid state reactive sintered Ce0.8Gd0.2O2−δ–FeCo2O4 composites. Issue 5 (31st October 2021) - Fischer, Liudmila; Neuhaus, Kerstin; Schmidt, Christina; Ran, Ke; Behr, Patrick; Baumann, Stefan; Mayer, Joachim; Meulenberg, Wilhelm A.
Abstract : Reactive sintering of composites for use as OTM is a promising method enabling lower sintering temperatures as well as low-cost raw materials. Phase formation and distribution during sintering plays a vital role in the performance of the composites. Abstract : Reactive sintering of dual phase composites for use as oxygen transport membranes is a promising method enabling lower sintering temperatures as well as low-cost raw materials. Ce0.8 Gd0.2 O2− δ –FeCo2 O4 composites with different nominal weight ratios from 60 : 40 to 90 : 10 are processed by reactive sintering of commercial Ce0.8 Gd0.2 O2− δ, Fe2 O3, and Co3 O4 powders. The phases formed in situ during sintering are investigated qualitatively and quantitatively by means of XRD and Rietveld refinement as well as transmission electron microscopy. Besides gadolinia-doped ceria, two Fe/Co-spinel phases are in equilibrium in agreement with the phase diagram. Moreover, a donor-doped GdFeO3 -based perovskite (Gd, Ce)(Fe, Co)O3 showing electronic conductivity is formed. Due to these intense phase reactions, the composition of each individual phase is assessed for all composites and their functional properties are discussed. The oxygen permeation performances of the composites are measured including their dependence on temperature and the potential limiting steps are discussed. The results reveal that the phase reactions support the formation of the desired mixed ionic electronic conductivity achieving percolation at low nominal spinel contents. The specific microstructure plays an extremely important role in the membrane performance and, thus, special attention should be paid to this in future research about dual phase membranes.